2019
DOI: 10.1016/j.kint.2018.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Regulated necrosis and failed repair in cisplatin-induced chronic kidney disease

Abstract: Cisplatin is an effective chemotherapeutic agent, but significant nephrotoxicity limits its clinical use. Despite extensive investigation of the acute cellular and molecular responses to cisplatin, the mechanisms of progression from acute to chronic kidney injury have not been explored. We used functional and morphological metrics to establish a time-point when the transition from acute and reversible kidney injury to chronic and irreparable kidney disease is clearly established. In mice administered 1 or 2 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 45 publications
1
65
0
1
Order By: Relevance
“…After receiving multiple cisplatin doses, patients may experience unresolved tubular injury, increasing susceptibility of further injury. 44,45 Although further research is needed with larger sample sizes to differentiate the contributions of risk factors and their associations, identified risk factors should be confirmed for identifying future individual cisplatin-associated AKI risk with a goal of early management. It remains unclear how cisplatin dose should be adjusted because of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…After receiving multiple cisplatin doses, patients may experience unresolved tubular injury, increasing susceptibility of further injury. 44,45 Although further research is needed with larger sample sizes to differentiate the contributions of risk factors and their associations, identified risk factors should be confirmed for identifying future individual cisplatin-associated AKI risk with a goal of early management. It remains unclear how cisplatin dose should be adjusted because of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The disconnection of the glomerular tubular junction is a common, but often undetected response to kidney injury 31 . ATG are seen in humans and rodent models of CKD [32][33][34][35][36][37][38] . The ATG were smaller than those with an intact glomerular-tubular junction outside of the lesions.…”
Section: Cationic Ferritin Is Not Toxic In the Ckd Modelmentioning
confidence: 99%
“…6,7 Another recent study using folic acid-induced nephropathy is very much in line with the suggested 2-wave model of injury in AKI, also confirming a role for necroptosis in the second wave of injury. 8 Together with the data by Landau et al, 1 necroptosis should be considered a therapeutic target for AKI.…”
mentioning
confidence: 92%
“…Mechanisms of AKI-to-CKD transition are subject to intensive research in the kidney community. In this issue of Kidney International, Landau et al 1 report a molecular 2-hit model of AKI-to-CKD transition induced by cisplatin.…”
mentioning
confidence: 99%
See 1 more Smart Citation